A New Method of Modeling for Cuk Converter Based on Signal Flow Graph Approach and its Control by using a Mixed Sensitivity Type Robust Technique - Leila Mohammadian; Ebrahim Babaei; Mohammad Bagher Bannae Sharifian (مجله مدل سازی در مهندسی, 2017)
In this paper, a new method based on signal flow graph is proposed for modeling a Cuk converter. Furthermore, the original signal flow graph based method suggested in literature is also implemented on the Cuk converter. The proposed method is very simple in the process, compared to other methods of modeling and the old method of signal flow graph. By using signal flow graph approach the three models of small signal, large signal and steady state are extracted. Also, without adding any additional computation, the desired transfer function between any two state variables of the circuit is extractable. After modeling the converter, a controller design problem for the Cuk converter will be discussed. A robust control method is proposed for controlling the system. It will be shown that, although the switching converter has a nonlinear nature, but this does not affect the controller design problem. By using a linear controller with parameters tuned with a robust method of mixed sensitivity type, controlling the converter is possible.